Pengaruh leverage, likuiditas, dan capital intensity terhadap tax avoidance dengan komite audit sebagai variabel moderating - Khasanah, Fitriyatul; Indriyani, Fany (Journal of Accounting and Digital Finance, 2021)
The purpose of this study was to determine the effect of Leverage, Liquidity, and Capital Intensity on Tax Avoidance with Audit Committee as a Moderating Variable in Companies Listed in the Jakarta Islamic Index (JII) 2015-2020. This research is included in the category of quantitative research with a sample selection model using purposive sampling. The selected sample is eight companies. The research data was analyzed using the moderated regression analysis method. The results showed that partially the leverage variable had a negative and significant effect on tax avoidance. The liquidity variable had a negative and insignificant effect on tax avoidance. The capital intensity variable had a positive and insignificant effect on tax avoidance. Meanwhile, simultaneously the variables of leverage, liquidity, and capital intensity cannot affect tax avoidance (ETR). Based on the Moderated Regression Analysis (MRA) test results, the moderating variable is that the audit committee can moderate the effect of leverage on tax avoidance, and the audit committee cannot moderate the effect of liquidity and capital intensity on tax avoidance.